2012
DOI: 10.7881/dentalmedres.32.189
|View full text |Cite
|
Sign up to set email alerts
|

Survey on the Issues and the Changes of Oral Health Condition of Inpatients in the Intensive Care Unit

Abstract: Abstract:The aim of this study was to consolidate oral health management systems in the acute stages. The practical status of oral health in perioperative patients and improvements achieved through coordinated oral health care were investigated. Subjects of the present study were 87 patients who underwent oral intubation in the intensive care unit (ICU). These patients attended an oral health care center from October 2010 to March 2011. Dentists rated the oral status of subjects within 24 h of admission to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…When xerostomia was present, it has been said that the risk of pneumonia increased, normal bacterial flora of the oral cavity, such as candida, also increased, as well as the changes in oral bacterial flora (Fields, 2008). It has also been reported that because orally intubated patients continue to have their mouths open, xerostomia often occurs (Ooka et al, 2013;2012). For this reason, pathogenic bacteria, including bacteria that causes pneumonia increase because of xerostomia and are thought to be related to occurence of VAP through the intubation tube.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When xerostomia was present, it has been said that the risk of pneumonia increased, normal bacterial flora of the oral cavity, such as candida, also increased, as well as the changes in oral bacterial flora (Fields, 2008). It has also been reported that because orally intubated patients continue to have their mouths open, xerostomia often occurs (Ooka et al, 2013;2012). For this reason, pathogenic bacteria, including bacteria that causes pneumonia increase because of xerostomia and are thought to be related to occurence of VAP through the intubation tube.…”
Section: Discussionmentioning
confidence: 99%
“…The disease names of the control subjects were extracted from the hospital medical records. Based on the criteria of preceding studies, we classified the principal diseases into four groups: Cerebrovascular diseases; pulmonary diseases; gastrointestinal diseases; and circulatory diseases (Ooka et al, 2013;2012). Subject attributes and representative principal diseases are shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%